Natural Revolution: Sharing value with the first owners. The case of AJE in Peru - Landeo, Romina (2023)
This study reveals how a company designed and developed a shared value initiative from a new product line, contributing to the sustainable development goals in Peru. The paper aims to identify the main characteristics of the collective impact achieved by Shared Value strategies of the Peruvian multinational company, AJE Group. The authors use an empirical case study of one of the biggest multinational companies in Peru to build upon Kramer’s model for shared value initiatives and analyze each of its five elements for shared value. The findings of this paper allow practitioners, as well as policy-makers, to identify sustainable managerial practices and opportunities for sustainability-oriented public policy design which can be implemented in other organizations.